A comparative study of the main mechanisms controlling indoor air pollution in residential flats - Halios, C.C.a; Helmis, C.G.a; Eleftheriadis, K.b; Flocas, H.A.a; Assimakopoulos, V.D.c (Water, Air, and Soil Pollution, 2009)
The relative contribution of the main mechanisms that control indoor air quality in residential flats was examined. Indoor and outdoor concentration measurements of different type pollutants (black carbon, SO 2, O 3, NO, NO 2,) were monitored in three naturally ventilated residential flats in Athens, Greece. At each apartment, experiments were conducted during the cold as well as during the warm period of the year. The controlling parameters of transport and deposition mechanisms were calculated from the experimental data. Deposition rates of the same pollutant differ according to the site (different construction characteristics) and to the measuring period for the same site (variations in relative humidity and differences in furnishing). Differences in the black carbon deposition rates were attributed to different black carbon size distributions. The highest deposition rates were observed for O 3 in the residential flats with the older construction and the highest humidity levels. The calculated parameters as well as the measured outdoor concentrations were used as input data of a one-compartment indoor air quality model, and the indoor concentrations, the production, and loss rates of the different pollutants were calculated. The model calculated concentrations are in good agreement with the measured values. Model simulations revealed that the mechanism that mainly affected the change rate of indoor black carbon concentrations was the transport from the outdoor environment, while the removal due to deposition was insignificant. During model simulations, it was also established that that the change rate of SO 2 concentrations was governed by the interaction between the transport and the deposition mechanisms while NO X concentrations were mainly controlled through photochemical reactions and the transport from outdoors. © 2009 Springer Science+Business Media B.V.
Keywords: Air quality; air sparging; article; Athens; atmospheric deposition; Atmospheric humidity; atmospheric pollution; Black carbon; building; calculation; Carbon black; Comparative studies; comparative study; Concentration (process); Controlling parameters; Deposition; Deposition mechanism; Deposition rates; Experimental data; experimental study; Feature extraction; Greece; humidity; Humidity levels; indoor air; Indoor air pollution; Indoor air quality; Indoor chemistry; Indoor concentration; Indoor pollution; Input datas; Loss rates; Model simulation; Moisture; nitrogen dioxide; nitrogen oxide; Outdoor concentrations; Outdoor environment; Ozone; Photochemical reactions; photochemistry; pollutant removal; pollutant transport; Pollution; pollution control; pollution transport; Quality control; Relative contribution; Relative humidities; residential area; room ventilation; simulation; Simulators; sulfide; Ventilation; Ventilation rate